2022
DOI: 10.1080/15569527.2022.2136193
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical dexamethasone eye drops in preventing ocular inflammation and cystoid macular edema following uncomplicated cataract surgery with or without injection of a single dose perioperative subtenon triamcinolone acetonide

Abstract: Purpose: To evaluate the efficacy and safety of topical dexamethasone (DEX) eye drops in combination with a single perioperative subtenon triamcinolone acetonide (sTA) injection versus conventional topical DEX eye drops in the prevention of ocular inflammation and cystoid macular edema following cataract surgery. Materials and methods: Medical records of 245 eyes of 245 patients who underwent uncomplicated cataract surgery were analyzed in this retrospective controlled clinical study. Topical DEX eye drops wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“… 33–36 Prior studies on dropless cataract surgery using triamcinolone injected approximately 3.5 mm or 10 mm posterior to the limbus did not result in greater risk for IOP increase postoperatively. 2 , 28 Our injection distance was within range of these studies, at 5 mm posterior to the limbus. Herschler 34 reported on a small series of 13 eyes receiving 40 mg of triamcinolone for various inflammatory conditions, 10 of which were in the anterior sub-Tenon’s space, and all 10 of which experienced an IOP increase.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“… 33–36 Prior studies on dropless cataract surgery using triamcinolone injected approximately 3.5 mm or 10 mm posterior to the limbus did not result in greater risk for IOP increase postoperatively. 2 , 28 Our injection distance was within range of these studies, at 5 mm posterior to the limbus. Herschler 34 reported on a small series of 13 eyes receiving 40 mg of triamcinolone for various inflammatory conditions, 10 of which were in the anterior sub-Tenon’s space, and all 10 of which experienced an IOP increase.…”
Section: Discussionsupporting
confidence: 72%
“…Steroid depot injections may provide better postoperative inflammation control than topical steroid drops alone, though findings from existing studies are mixed. [3][4][5][6]28 Several studies have found that eyes receiving steroid injections have lower incidence of cystoid macular edema (CME) following cataract surgery, but there were no significant visual acuity differences between the steroid depot and topical steroid groups on postoperative follow-up. 3,28 Other studies found no significant difference in CME but did find lower rates of anterior chamber cell and flare, without a difference in postoperative visual acuity between steroid depot and topical steroid eyes (although the study examiners were not blinded to the type of steroid patients received).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, TA-NC exhibited a superior effect on fogginess attenuation than Fortcinolona ® 40 at the same dose, which could be explained by the higher drug saturation concentration that allows a larger amount of available dissolved molecules to exert a pharmacological effect. Similarly, the demonstrated therapeutic efficacy of TA-NC was achieved in this in vivo model by testing half the dose typically used for injection of TA nanosuspensions [ 34 , 35 , 36 , 37 ] such as off-label Fortcinolona ® 40 in the clinical treatment of ocular inflammations such as uveitis. Thus, TA-NC could result in a promising approach to administering lower doses of corticosteroids or decreasing the frequency of administration of the therapeutic scheme.…”
Section: Discussionmentioning
confidence: 99%